The role of Biofilm for Pseudomonas aeruginosa to resistance ultraviolet and MIC concentration for antibiotics: Ahmad, M. T. 1, A.A. Abed2 and I. A. Abed - تركي, احمد محمد (The Iraqi Journal of Veterinary Medicine, 2012)
The present study is conducted to in restigate the bacteria Pseudomonas aeruginosa, the impact of ultraviolet on the bacterial isolates under study and the resistance of these isolates to ultraviolet are studied in comparison to two standard isolates ( E . coli and Staphylococcus aureus ) which are considered sensitive to ultraviolet . The natures of the resistance of the isolates, under study, are also being investigated against the different antibiotics. The isolates are subjected to a test to examine their sensitivity to (12) types of antibiotics used routinely in the treatment of various infection of these bacteria. They are (streptomycin , cephalothin ,Gentamycin , cefotaxime ,nitrofurantion ,ampicillin, amoxicillin, rifampin, lincomycin, tetracycline, erythromycin and ciprofloxacin ).The lowest concentration installer ( MIC ) is also testified in accordance with six types of antibiotics (streptomycin, cefotaxime , rifampin , nitrofurantion , Gentamycin , amoxicillin ).The biologic effectiveness of the overlap between the bacterial isolates , under study, is examined against four bacteria (klebseilla pneumonia , Staphylococcus aureus , Enterobacter , Proteus ) The result of using the ultraviolet with different wavelength show the ability of the five local isolates used to resistance of ultraviolet reaching (180 s.) in comparison to the isolates E.coli and staph. aureus in which the ratio of killing is %100 at a time of exposing 40 , 60 sec. respectively. The results indicated that the five local bacterial isolates have high resistance to the most tested antibiotics, It is shouted that all of them have resistance to (erythromycin , tetracycline , lincomycin , Gentamycin ) but they are sensitive towards antibiotic streptomycin . as for the other antibiotics , over can find that the isolates are varied of them for being resisting or sensitive towards them .The results of testing the inhabited effectiveness of the five bacterial isolates towards some other bacterial isolates show the efficiency of the five local isolates in the inhabitation of growth of the five studied bacterial isolates.